Service-Learning and First-Generation University Students: A Conceptual Exploration of the Literature. (December 2019) - Taylor, Alison; Yochim, Lorin; Raykov, Milosh
Background: Despite increased access to higher education in recent decades, first-generation (first-gen) university students continue to face challenges with persistence and completion. Recommended responses by universities include exposing these students to "high-impact" educational practices.Purpose: This article examines the potential of one of these practices—service-learning—to address the disadvantages faced by first-gen students.Methodology/Approach: We review the literature on first-gen students and service-learning and offer a conceptual critique of dominant approaches.Findings/Conclusions: Dominant conceptions of service-learning treat first-gen students as a homogeneous, deficient group and reduce learning to an input-environment-output model. We argue for a more conceptually nuanced understanding of the reasons for the cultural mismatch often experienced by underrepresented groups of students.Implications: The conceptual resources offered in this article are intended to help researchers and policy makers undertake research that captures the diversity and richness of students' lives and leads to more equitable practices.